Kontaminasi Logam Berat pada Tanaman Pangan & Implikasinya Terhadap Keamanan Pangan di Indonesia - Salmina Ulfa; Nidaul Ulfa; Aura Angelica Kirana; Firdus Firdus; Muhammad Nasir; Alia Rizki (Jurnal Bioleuser, 2026)
Heavy metal contamination in agricultural soils has become a serious threat to crop productivity, food safety, and human health. Sources of contamination include both geogenic processes and anthropogenic activities. These human activities range from the use of fertilizers and pesticides to the disposal of industrial waste and irrigation with contaminated water. These various factors contribute to increased levels of cadmium (Cd), lead (Pb), and arsenic (As) in soil and food crops. The bioavailability of these metals is largely controlled by soil properties, including pH and organic matter content, as well as rhizosphere processes that determine metal uptake, translocation, and accumulation in edible plant tissues. At the molecular level, the uptake and transport of heavy metals involve specific transporters, such as OsNramp5 for Cd and Lsi1/Lsi2 for As, which function together with chelation mechanisms, vacuolar detoxification, and the regulation of defense-related genes and stress hormones. Recent studies highlight the importance of multi-metal interactions, including antagonistic relationships between zinc (Zn) and cadmium (Cd) and competition between arsenic (As) and silicon (Si), as well as the role of soil and rhizosphere microbiomes in mobilizing or immobilizing heavy metals. The accumulation of heavy metals in food crops has been shown to increase both carcinogenic and non-carcinogenic health risks for consumers, particularly in agricultural areas located near industrial zones or those using wastewater for irrigation. Therefore, understanding the sources, bioavailability, and mechanisms of heavy metal accumulation—together with molecular and microbiological approaches—is essential for developing effective mitigation strategies and breeding safer food crops.